Pengaruh Pemesinan Bubut Kering Terhadap Daya Motor Listrik Dengan Menvariasikan Putaran Spindel - Tertius Ulaan; Rudy Poeng; Irvan Rondonuwu (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2022)
In a metal cutting process, especially a lathe that can cut the workpiece into the desired product, it is generally done with dry machining (without using cooling media). This is done because to reduce the cost of machining is done. (Rochim, 2007) The purpose of this study was to obtain the effect of dry lathe machining on electric motor power by varying the spindle rotation. The method used in this study is the test method on the KNUT 1000 A lathe in the Unsrat Mechanical Engineering Laboratory. The results of this study indicate that the spindle rotation speed is increased from 300 rpm to 1600 rpm, the electric motor power increases from 1216 W to 1794 W, so that dry lathe machining affects the use of electric motor power with varying spindle rotation.